1999
DOI: 10.1007/s002489900136
|View full text |Cite
|
Sign up to set email alerts
|

Moving Waves of Bacterial Populations and Total Organic Carbon along Roots of Wheat

Abstract: > Abstract To determine if spatial variation in soluble carbon sources along the root coincides with different trophic groups of bacteria, copiotrophic and oligotrophic bacteria were enumerated from bulk soil and rhizosphere samples at 2 cm intervals along wheat roots 2, 3, and 4 weeks after planting. There was a moderate rhizosphere effect in one experiment with soil rich in fresh plant debris, and a very pronounced rhizosphere effect in the second experiment with soil low in organic matter. We obtained wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(75 citation statements)
references
References 28 publications
3
71
0
1
Order By: Relevance
“…The shifts in the fungal community patterns most likely occurred because of changing root morphology and root exudation patterns during plant development (5,28). The release of organic substances by plant roots has an interesting ecological aspect, since it influences the nutrient availability in the rhizosphere and indirectly acts on the soil microorganisms that in turn influence plant growth (9,10,15,34,38,45,46). Temporal changes in the bacterial communities in the rhizosphere were indicated by different cultivation-based studies (2,21,25).…”
Section: Discussionmentioning
confidence: 99%
“…The shifts in the fungal community patterns most likely occurred because of changing root morphology and root exudation patterns during plant development (5,28). The release of organic substances by plant roots has an interesting ecological aspect, since it influences the nutrient availability in the rhizosphere and indirectly acts on the soil microorganisms that in turn influence plant growth (9,10,15,34,38,45,46). Temporal changes in the bacterial communities in the rhizosphere were indicated by different cultivation-based studies (2,21,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, both studies followed potential temporal shifts in the composition of bacterial rhizosphere communities for a much shorter period of time (up to 36 days after sowing and up to 10 weeks after planting, respectively) under growth chamber conditions, one factor which might have contributed to the contrasting results. Semenov et al (43) found a moderate rhizosphere effect in one experiment with soil rich in fresh plant debris and a very pronounced rhizosphere effect in a second experiment with soil low in organic matter content using cultivation techniques (by enumeration of copiotrophic and oligotrophic bacteria).…”
Section: Discussionmentioning
confidence: 99%
“…This ecological behavior is more consistent with organisms that are influenced by bulk soil (for example soil organic matter). Soil organic matter can be a significant source of carbon for rhizosphere organisms (Toal et al, 2000), and high levels of organic matter and nutrients, such as those that are supplied via compost amendment, can influence the strength of the observed rhizosphere effect (Semenov et al, 1999). Although Chryseobacterium spp are found frequently in organic-rich environments such as composted materials (Ryckeboer et al, 2003), these organisms are not particularly well known as rhizosphere organisms, even though they have been previously detected in or isolated from rhizosphere environments (McSpadden Gardener and Weller, 2001;Young et al, 2005;Park et al, 2006).…”
Section: Seed and Root-colonizing Bacteria Sj Green Et Almentioning
confidence: 99%